(untitled) (Medical Forum Monthly, 2024)
Frequency of Cardiomyopathy in Beta Thalassemic Children 3-6 Rahida Karim 2. Faiz ur Rehman 3. Amjad Zaman 4. Matti ur Rehman 5. Jehanzeb Medically Unexplained Symptoms and Emotional Disorders Among School Children 7-10 Ayesha Sarwat 2. Muzzamil Ejaz 3. Muhammad Rafique 4. Abid Hussain Effects of Medical Study on Sports Activities of Medical Students in Azad Kashmir 11-15 Malik Asrar Ahmed 2. Amir Ahmed Assessment of Antiphospholipid Antibodies in Women with Recurrent Miscarriage at GMMMC,Sukkur 16-19 Arshad Hussain Laghari 2. Akhtar Hussain Samoo 3. Khalid Ahmed Qureshi Frequency of Retinoblastoma According to Age, Gender and Laterality 20-23 Syed Muhammad Ishaque 2. Shahnaz Imdad Kehar 3. Saba Sattar Effectiveness of Incentive Spirometry in Preventing Postoperative Pulmonary Complications after Laparotomy 24-26 Muhammad Imran 2. Ashfaq Ahmed Javed 3. Muhammad Asif Awareness and Acceptance of Family Planning in Patients Coming to Gynae Department of G.Khan Teaching Hospital 27-291. Sadia Nazir 2. Majeed ullah Buzdar 3. Abrar Khosa Effects of Lactobacillus (Acidophilus) on Cutaneous Wound Repair with Respect to Neutrophil Count in Comparison with Steroid 30-32 Hina Khan 2. Muhammad Asif Sheikh 3. Mazhar ul Haque 4. Aneela Qureshi 5. Amin Fahim 6. Nazia Qamar 7. Adnan Anwar Diagnostic Accuracy of Mammography in Characterization of Palpable Breast Lumps in Benign and Malignant: Keeping Histopathology as a Gold Standard 33-36Faiza Farooq Effective Time Management Practices: Awareness and Perceptions 37-40 Gulshan Trali 2. Asifa Majeed To Detect the Dyslipidemia in Patients with Rheumatic Arthritis 41-44 Abdul Aziz Saheto 2. Abdul Qadir Khan 3. Nasrullah Amir An Early Experience of Laproscopic Cholecystectomy from K.M.C/Civil Hospital Khairpur Mir’s 45-48 Abdul Malik Sangri 2. Azad Lashari 3. Zulfiqar Shar 4. Ali Gohar Bozdar 5. Khush Mohammad Sohu 6. Roshan Ali Solangi Acute Poisoning and its Medico-legal Aspects in Patients Presenting at a Tertiary Care Hospital of Sindh 49-52 Waheed Ali 2. Pardeep Kumar 3. Mohammad Qasim 4. Aisha Health Behaviors and Loneliness in Young Adults 53-56 Husna Saeed 2. Sarah Shaheed Relationship Between Nutritional Health and Academic Performance of School Going Children 57-61 Uzma Ashiq Khan 2. Sarah Shaheed Risk Factors for Renal Dysfunction after Total Hip Joint Replacement in One Territory Care Hospital in Peshawar 62-65 Mohammad Tariq Ijaz Afridi 2. Farooq Munfaet Ali Khan 3. Tanveer Sadiq Chaudhry 4. Asnad